Residential Buildings : A Typology - Pfeifer, Günter; Brauneck, Per (Birkhäuser, 2015)
To continue developing existing building types in an intelligent way is a crucial task in the field of residential building. For this typology of residential buildings, the authors have developed systematic new presentations of most innovative types. Each individual part lays out the possibilities for using and transforming a particular form of residential structure: the courtyard house, the row house, the town house and the freestanding house.